Acupuncture Care in Patients with Post-Stroke Dementia: A Case Report - Sissy Peleh; Amal Prihatono; Mayang Wulandari (CV. Publikasi Indonesia, 2026)
Stroke remains a major global health concern due to its high mortality and disability burden, with post-stroke dementia emerging as a significant complication that affects cognitive function and patient independence. Acupuncture has been proposed as a complementary therapy to support neurological rehabilitation through its potential effects on cerebral blood flow, neuroplasticity, and cognitive recovery. This study aimed to describe the application of acupuncture care and evaluate changes in cognitive function in a patient with post-stroke hemorrhagic dementia using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina). This study employed a descriptive case report approach involving a 60-year-old male patient diagnosed with post-stroke hemorrhagic dementia accompanied by chronic lacunar infarction and uncontrolled hypertension. The patient received acupuncture therapy three times per week for four weeks, resulting in a total of twelve treatment sessions. Cognitive function was assessed before and after the intervention using MoCA-Ina. The results demonstrated an improvement in the total MoCA-Ina score from 4 at baseline to 11 after acupuncture therapy. Improvements were observed in the naming, attention, language, abstraction, delayed recall, and orientation domains, while executive function remained unchanged. These findings suggest that acupuncture care may have potential benefits in supporting cognitive rehabilitation among patients with post-stroke dementia. However, further studies involving larger sample sizes and more rigorous research designs are required to confirm its clinical effectiveness and establish standardized acupuncture protocols for post-stroke cognitive rehabilitation.